Refleksi Filosofis terhadap Gender dalam Budhisme (Studi atas Kitab Aganna Sutta) - Abd. Rahman Effendi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
The difference of gender does become a problem during generate no grind and injustice. But practically, difference of gender exactly have dribbled, bear, and attitude of practice discriminating one of gender which is on generally woman clan.The reality progressively crystal, when religion as guidance of human life entangled for legitimate of injustice of gender which have happened. Religion interpreted in such a manner to maintain society structure which always grind woman clan.As for Buddhism, religion which emerge as criticism to previous religion that is Hindhuism, its growth of indication have discredited role of women clan at religion region. Though teachings od Siddharta Gautama basiclly very egalitarian and carry the spirit is humanity. Phenomenon which this contradiction if careful come from existence of interpretation embrace of religion of Buddha which harming woman clan.To return purity of teaching of Siddarta Gautama felt important to conduct re-interpretation by critic-philosophy to holy book of Buddism without again side at certain gender. As for one of the book becoming study focus is book of Aganna Sutta a holy book of Buddhism discussing to regarding human being origin. Why book is chosen? Because book of Aganna Sutta besides discussing human being origin at the same talk about the nature of human being base and what conducted by women and men when the first meet which still not yet recognized to feel to in command.